Cultural Impact on Medication Instructions: The Case of the Turkish Teaspoon. Issue 2 (June 2018) - Kannan, Lakshmi; Blocher, Nissa
Abstract : Abstract: Medication errors are preventable events related to inappropriate medication use that could potentially result in patient harm. Here we present a patient encounter that has exemplified the importance of appropriate communication and the inevitable role of every individual in ensuring appropriate prescription medication use. Multidisciplinary efforts are required to ensure patient safety in today's systems based practice. This case highlights cultural barriers to the practice of medicine and the growing need to explore and address them appropriately.